Eugenics and genetic determinism. A simple solution for a complex problem - Villela Cortés, Fabiola (Acta Bioethica, 2017)
The main goals of this article are first, to present the current situation of eugenics, how it developed during the XX century, the main characteristics of the “new eugenics” and the two current ethical-philosophical postures (bioconservatives and transhumanist). Second, to sustain the existence of genetic determinism in both postures, provoking the actual eugenic discourse is being use to propose simple solutions (genetic ones) to complex problems (conducts or social). Third and last, is to question the motivations laying in the implementation of the new eugenics.